2021
DOI: 10.3390/cells10123533
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Binding Pattern of Geraniol with Acetylcholinesterase through In Silico Docking, Molecular Dynamics Simulation, and In Vitro Enzyme Inhibition Kinetics Studies

Abstract: Acetylcholinesterase (AChE) inhibition is a key element in enhancing cholinergic transmission and subsequently relieving major symptoms of several neurological and neuromuscular disorders. Here, the inhibitory potential of geraniol and its mechanism of inhibition against AChE were elucidated in vitro and validated via an in silico study. Our in vitro enzyme inhibition kinetics results show that at increasing concentrations of geraniol and substrate, Vmax did not change significantly, but Km increased, which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 61 publications
(77 reference statements)
1
15
0
Order By: Relevance
“…The MeOH extract was found to be a noncompetitive inhibitor of α-amylase and a competitive inhibitor of AChE ( Figure 4 ). On the contrary, the standard drugs, acarbose and tacrine, showed competitive and noncompetitive inhibition of α-amylase and AChE, respectively, which is in agreement with previous reports [ 32 , 39 ]. It is evident that plant extracts exhibit competitive and noncompetitive inhibition due to the presence of a variety of bioactive compounds [ 59 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The MeOH extract was found to be a noncompetitive inhibitor of α-amylase and a competitive inhibitor of AChE ( Figure 4 ). On the contrary, the standard drugs, acarbose and tacrine, showed competitive and noncompetitive inhibition of α-amylase and AChE, respectively, which is in agreement with previous reports [ 32 , 39 ]. It is evident that plant extracts exhibit competitive and noncompetitive inhibition due to the presence of a variety of bioactive compounds [ 59 ].…”
Section: Discussionsupporting
confidence: 93%
“…Antioxidants from natural sources, such as plants, and their secondary metabolites are efficient quenchers of free radicals and interrupt their production. Their consumption helps in the management of oxidative stress and in preventing the onset of several diseases such as DM and AD [ 2 , 36 , 37 , 38 , 39 ]. Numerous in vitro and in vivo studies have shown that C. nocturnum leaf extracts have antifungal, antibacterial, antidiabetic, and wound healing properties [ 22 , 24 , 27 , 28 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy minimisation was achieved using the steepest approach of 8 ps. The machine was balanced at 40 ps when the temperature was raised to 300 K. The simulations at 10 ns were performed at 1 bar and at the temperature of 300 K. Finally, an all-bond restriction was employed to keep the ligand from migrating during molecular dynamics [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…As brain-derived neurotrophic factor (BDNF) or abrineurin has a critical role in remodeling the cognitive functions and remodeling of synapses, restoring the BDNF expression could be a therapeutic pathway [10]. Meanwhile, a variety of phytochemicals and natural products, like compounds, have been reported as potent antidiabetic, antimicrobial, antioxidant, gastro-protection, geno-protective, hypolipidemic and neuroprotective agents [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Studies have also shown good improvements in neurodegenerative diseases through the use of phytochemicals [27], and indicating that phytochemicals, which are chemical compounds extracted from plants, exhibit possible health promotion properties.…”
Section: Introductionmentioning
confidence: 99%